Effects of Different Proportions of Aluminum oxide Nanoparticles for 6063 AA Nano-Composite on Mechanical Properties - Mamoon A A Al-Jaafari (Peerian Journals Publishing, 2023)
This This work aims at an applied study of the process of adding different percentages of aluminum oxide to aluminum alloys that are widely used and the effect of these additives on a major set of physical properties, and the results obtained showed an increase in the strength and quality of samples reinforced with nano-materials compared to the base material
Keywords: Mechanical properties; 6063AA; Aluminum oxide; Nano Composite